Speech Acts Used in 2024 General Election Discount Promo in Instagram - Giyatmi, Giyatmi; Arumi, Sihindun; Wijayava, Ratih (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
The research aims to describe types of speech acts employed in the context of the General Election 2024 discount promotion by making an intersection between Yule’s and Searle’s classification of speech acts. The research belongs to descriptive qualitative research. The writers only chose discount promo utterances using English as the data. They are from @giladiskon on February 13-14, 2024. The writers used take notes to in collecting data. The data analysis process includes data reduction, data display, and conclusion. There were 36 utterances of discount promo. The writers found 28 types of direct speech acts with statement sentences (3) and imperative sentences (25). These direct speech acts consist of direct-directive speech acts (3) for request, direct-commissive speech acts (23) for promises and offers, and direct-representative speech acts (2) for information. Meanwhile, there are 8 indirect speech acts with statement sentences expressing promise and offer. Direct speech acts are frequently applied because they are regarded as a more straightforward means of conveying intention. Direct and indirect-commissive speech acts are commonly used in advertisements to convey promises and offers, to increase voter confidence in the perceived benefits of taking part in the process of electing.